Nickel selenide / tin selenide heterojunction composite material and preparation method and application thereof

Through the preparation of nickel selenide/tin selenide heterojunction composite materials, the problem of insufficient structural stability and conductivity of tin selenide electrode materials in sodium ion batteries is solved, and the battery performance with high energy density and long cycle life is achieved.

CN119650642APending Publication Date: 2025-03-18GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411818058.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

As an electrode material, tin selenide in sodium ion batteries has structural collapse and powdering problems, resulting in poor circulation performance and low conductivity limits the transmission speed of electrons and Na+.

Method used

The nickel selenide/tin selenide heterojunction composite material is prepared by hydrothermal reaction and calcination reaction to form nanosheets with spherical morphological structures. The connection interface between nickel selenide and tin selenide forms a heterojunction to improve the conduction performance of electrons and ions.

Benefits of technology

The electrochemical performance of sodium ion batteries is significantly improved, including excellent sodium ion storage performance and cycle stability. The first charging specific capacity is 350mAh/g~450mAh/g, and the charging specific capacity is 300mAh/g~400mAh/g after 500 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650642A_ABST
    Figure CN119650642A_ABST
Patent Text Reader

Abstract

The invention provides a nickel selenide / tin selenide heterojunction composite material as well as a preparation method and application thereof, and relates to the technical field of battery negative electrode materials. The nickel selenide / tin selenide heterojunction composite material is of a ball-flower morphology structure, the ball-flower morphology structure is formed by stacking a plurality of nanosheets, the nanosheets comprise nickel selenide and tin selenide loaded on the surface of the nickel selenide, and a heterojunction is formed on a connection interface of the nickel selenide and the tin selenide. The preparation method of the nickel selenide / tin selenide heterojunction composite material comprises the following steps: (1) dissolving tin chloride pentahydrate and nickel chloride hexahydrate in water to form a reaction solution, adding alkali to adjust the pH value of the reaction solution to 8-12, and carrying out hydrothermal reaction to obtain a precursor; and (2) uniformly mixing the precursor and selenium powder, and performing calcination reaction in an inert atmosphere to obtain the nickel selenide / tin selenide heterojunction composite material. The nickel selenide / tin selenide heterojunction composite material prepared by the invention can effectively improve the conduction performance of electrons and ions, and has excellent sodium ion storage performance and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery negative electrode materials, and in particular to a nickel selenide / tin selenide heterojunction composite material and a preparation method and application thereof. Background Art

[0002] In recent years, due to the surging demand for energy storage and the deteriorating ecological environment, secondary batteries have attracted widespread attention due to their excellent properties such as high energy density and long cycle life. Sodium-ion batteries (SIBs) are expected to become an alternative to lithium-ion batteries (LIBs) due to their low cost and abundant reserves. However, the relatively large radius of sodium ions This may lead to slower electrode reaction kinetics and unsatisfactory electrochemical performance. Therefore, designing low-cost electrode materials with fast reaction kinetics remains a major challenge.

[0003] Alloy metal selenides (MSex, M is Bi, Sb, Sn, etc.) are considered to be the most promising electrode materials for SIBs due to their unique electrochemical properties, special structures and high theoretical capacities. In addition, compared with metal oxides, MSex exhibits higher conductivity and adjustable energy gap. Moreover, the weak selenium bonds present in MSex can promote electrochemical reactions and improve the reversibility of reactions. As a typical MSex material, tin selenide is regarded as one of the most promising electrode materials for high energy density SIBs due to its layered structure, high theoretical capacity and eco-friendliness. However, the practical application of tin selenide in SIBs is limited by its intrinsic defects. The volume expansion during the sodium insertion / extraction process can lead to the collapse and pulverization of the material structure, resulting in poor cycling performance. Moreover, the low conductivity of MSex limits the electrons and Na + transport during the conversion reaction, resulting in slow reaction kinetics.

[0004] In order to improve the electrochemical performance of tin selenide as an electrode material for SIBs, various rational design methods have been explored, including carbon coating, nanostructure construction, and defect introduction. In addition, heterostructure engineering has been proven to be an effective strategy to improve the structural stability and reaction kinetics of materials. The built-in electric field generated by the two materials with different band gaps and Fermi levels in the heterostructure can accelerate electron transport and enhance reaction kinetics, and the lattice distortion of the heterointerface can provide more active sites for sodium ion storage. Therefore, when heterojunction materials are used as negative electrode materials for SIBs, the battery energy density and cycle performance can be effectively improved. Summary of the invention

[0005] The purpose of the present invention is to provide a nickel selenide / tin selenide heterojunction composite material and its preparation method and application. The nickel selenide / tin selenide heterojunction composite material of the present invention can effectively improve the conductivity of electrons and ions, and has excellent sodium ion storage performance and cycle stability.

[0006] To achieve the above-mentioned purpose, the first aspect of the present invention provides a nickel selenide / tin selenide heterojunction composite material having a flower ball morphology structure, wherein the flower ball morphology structure is formed by stacking a number of nanosheets, wherein the nanosheets include nickel selenide and tin selenide loaded on the surface of the nickel selenide, and the connection interface between the nickel selenide and the tin selenide forms a heterojunction.

[0007] Compared with the prior art, the nickel selenide / tin selenide heterojunction composite material of the present invention can effectively improve the conductivity of electrons and ions, and has excellent sodium ion storage performance and cycle stability. The specific mechanism is as follows.

[0008] (1) Nickel selenide, as a transition metal selenide, shows good application potential in battery negative electrode materials due to its excellent electronic conductivity and high electrochemical stability. Specifically, nickel selenide can effectively promote electronic conduction during battery charging and discharging, and due to the unique properties of transition metals, it may provide higher energy density during discharge, thereby enhancing the overall performance of the battery. Tin selenide is a material with significant thermoelectric properties, especially in low dimensions (such as two-dimensional structures), showing high electrical conductivity and good ionic conductivity. These characteristics enable tin selenide to significantly increase the ion transfer rate in battery applications, especially in negative electrode materials, thereby optimizing the battery's charge and discharge rate and improving cycle stability. The present invention combines nickel selenide and tin selenide to form a heterostructure, and the two can complement each other's respective advantages: nickel selenide provides good electronic conductivity, while tin selenide promotes ionic conductivity and thermal management.

[0009] (2) Since the band gaps of nickel selenide and tin selenide are 1.26 and 1.10 eV, respectively, they have different energy levels. Charge separation occurs at the contact interface between nickel selenide and tin selenide, where electrons are transferred from nickel selenide to tin selenide until the bottom of their conduction bands are at the same energy level, allowing electrons to transfer freely between the two phases of the heterojunction. In this process, positive charges accumulate on the nickel selenide side, while negative charges accumulate on the tin selenide side, thereby forming a self-built electric field from nickel selenide to tin selenide. Due to the lower electrostatic potential of tin selenide, it can effectively absorb sodium ions in the electrolyte and act as a sodium ion reservoir at the nickel selenide / tin selenide heterojunction, forming a so-called "ion reservoir". During the electrode reaction, although the electric field disappears due to charge neutralization, the sodium ions still maintain a high ion concentration in the ion reservoir and form a concentration gradient, which prompts the charge to be quickly transferred to the materials in contact on both sides, thereby achieving an improvement in the sodium ion adsorption capacity, sodium ion and electron migration rate, and structural stability. In addition, the uniformly distributed phase boundaries in the NiSe / SnSe heterostructure effectively maintain the Sn0 / Na2Se interface, which improves the reversibility of transformation / alloying while effectively suppressing electrode deformation and pulverization, further ensuring its structural stability during the cycling process.

[0010] In summary, the nickel selenide / tin selenide heterojunction composite material of the present invention

[0011] In some embodiments, the diameter of the flower ball morphology structure is 2 μm to 8 μm.

[0012] In some embodiments, the thickness of the nanosheets is between 50 nm and 100 nm.

[0013] In some embodiments, the thickness of tin selenide is 5 nm to 15 nm.

[0014] In some embodiments, nickel selenide has d(131)=0.195 nm.

[0015] In some embodiments, tin selenide has d(040) = 0.291 nm.

[0016] In some embodiments, the first charge specific capacity of the nickel selenide / tin selenide heterojunction composite material is 350 mAh / g to 450 mAh / g.

[0017] In some embodiments, the specific charge capacity of the nickel selenide / tin selenide heterojunction composite material after 500 cycles is 300 mAh / g to 400 mAh / g.

[0018] In some embodiments, the charge transfer resistance of the nickel selenide / tin selenide heterojunction composite material is 5Ω-30Ω.

[0019] The second aspect of the present invention provides a method for preparing a nickel selenide / tin selenide heterojunction composite material, comprising the steps of:

[0020] (1) dissolving tin chloride pentahydrate and nickel chloride hexahydrate in water to form a reaction solution, adding alkali to adjust the pH of the reaction solution to 8 to 12, and then performing a hydrothermal reaction. After the reaction is completed, the reaction solution is cooled to room temperature, washed, and dried to obtain a precursor;

[0021] (2) The precursor and selenium powder are mixed evenly and then calcined in an inert atmosphere to obtain a nickel selenide / tin selenide heterojunction composite material.

[0022] Compared with the prior art, the present invention uses tin chloride pentahydrate and nickel chloride hexahydrate as raw materials, and performs a hydrothermal reaction under the condition of pH 8 to 12. Under this condition, tin chloride pentahydrate and nickel chloride hexahydrate are dissolved to form Sn 2+ and Ni 2+ , while Sn 2+ and Ni 2+ With OH in aqueous solution -The precursor and selenium powder are calcined to form nickel selenide and tin selenide supported on the surface of nickel selenide, thus obtaining the nickel selenide / tin selenide heterojunction composite material of the present invention.

[0023] In some embodiments, the molar ratio of tin chloride pentahydrate to nickel chloride hexahydrate is 1:0.5-4.

[0024] In some embodiments, the base is selected from at least one of sodium hydroxide and potassium hydroxide.

[0025] In some embodiments, the temperature of the hydrothermal reaction is 140° C. to 180° C., and the time of the hydrothermal reaction is 12 h to 36 h.

[0026] In some embodiments, washing includes alcohol washing and water washing, the drying temperature is 120° C. to 150° C., and the drying time is 8 h to 12 h.

[0027] In some embodiments, the mass ratio of the precursor to the selenium powder is 1:1-4.

[0028] In some embodiments, the inert atmosphere includes at least one of nitrogen, argon, helium and neon, the calcination reaction temperature is 400°C to 800°C, the heating rate is 1°C / min to 10°C / min, and the holding time is 1h to 6h.

[0029] The third aspect of the present invention provides the use of the aforementioned nickel selenide / tin selenide heterojunction composite material or the nickel selenide / tin selenide heterojunction composite material prepared according to the aforementioned nickel selenide / tin selenide heterojunction composite material preparation method as a negative electrode material for a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the nickel selenide / tin selenide heterojunction composite material of Example 6 of the present invention;

[0031] Figure 2 is the XRD spectrum of the nickel selenide / tin selenide heterojunction composite material of Example 6 of the present invention;

[0032] Figure 3 HRTEM spectrum of the nickel selenide / tin selenide heterojunction composite material of Example 6 of the present invention;

[0033] Figure 4 is a HRTEM spectrum of the nickel selenide / tin selenide heterojunction composite material of Example 6 of the present invention at another magnification;

[0034] Figure 5This is a graph of the long cycle performance curve of the nickel selenide / tin selenide heterojunction composite material of Example 6 of the present invention. DETAILED DESCRIPTION

[0035] The invention provides a nickel selenide / tin selenide heterojunction composite material. The nickel selenide / tin selenide heterojunction composite material has a flower ball morphology structure, which is formed by stacking a plurality of nanosheets. The nanosheets include nickel selenide and tin selenide loaded on the surface of the nickel selenide, and a connection interface between the nickel selenide and the tin selenide forms a heterojunction.

[0036] The diameter of the flower ball structure is 2 μm to 8 μm. As an example, the diameter of the flower ball structure can be, but is not limited to, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4 ... The thickness of the nanosheet is 50nm to 100nm. As an example, the thickness of the nanosheet can be, but is not limited to, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm. The diameter of the flower ball structure of the present invention is 2 μm to 8 μm, and the thickness of the nanosheet is 50 nm to 100 nm. Within this range, it is not only conducive to releasing huge mechanical stress during repeated sodium embedding and de-embedding, but also can accelerate the electrolyte to active Na + Permeation rate of storage sites.

[0037] The thickness of tin selenide is 5nm to 15nm. As an example, the thickness of tin selenide can be, but is not limited to, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, and 15nm. Within this range, it has good electrical conductivity and good ion conductivity, which helps to improve the rate and cycle performance of the nickel selenide / tin selenide heterojunction composite material of the present invention.

[0038] The nickel selenide d(131)=0.195nm and the tin selenide d(040)=0.291nm are helpful to form a uniformly distributed nickel selenide / tin selenide heterostructure phase boundary interface and improve the structural stability of the heterojunction.

[0039] The nickel selenide / tin selenide heterojunction composite material of the present invention is used as a negative electrode active material in a sodium ion battery, and its initial charging specific capacity is 350mAh / g to 450mAh / g, and the charging specific capacity after 500 cycles is 300mAh / g to 400mAh / g, and the charge transfer resistance is 5Ω to 30Ω.

[0040] The method for preparing the nickel selenide / tin selenide heterojunction composite material of the present invention may include the steps of:

[0041] (1) dissolving tin chloride pentahydrate and nickel chloride hexahydrate in water to form a reaction solution, adding alkali to adjust the pH of the reaction solution to 8 to 12, and then performing a hydrothermal reaction. After the reaction is completed, the reaction solution is cooled to room temperature, washed, and dried to obtain a precursor;

[0042] (2) The precursor and selenium powder are mixed evenly and then calcined in an inert atmosphere to obtain a nickel selenide / tin selenide heterojunction composite material.

[0043] In step (1), the molar ratio of tin chloride pentahydrate to nickel chloride hexahydrate is 1:0.5-4. In some technical schemes, the molar ratio of tin chloride pentahydrate to nickel chloride hexahydrate is 1:1-4. In some technical schemes, the molar ratio of tin chloride pentahydrate to nickel chloride hexahydrate is 1:1-3. As an example, the molar ratio of tin chloride pentahydrate to nickel chloride hexahydrate can be, but is not limited to, 1:0.5, 1:0.8, 1:1, 1:1.5, 1:1.8, 1:2, 1:2.5, 1:3, 1:3.5, 1:4.

[0044] The water may be at least one of deionized water and purified water. In some technical solutions, the water is deionized water. In some technical solutions, the water is purified water. The alkali is selected from at least one of sodium hydroxide and potassium hydroxide. In some technical solutions, the alkali is sodium hydroxide. In some technical solutions, the alkali is potassium hydroxide.

[0045] The hydrothermal reaction can be carried out in a closed pressure vessel. In some technical solutions, the hydrothermal reaction can be carried out in a Teflon autoclave. The temperature of the hydrothermal reaction is 140°C to 180°C. In some technical solutions, the temperature of the hydrothermal reaction is 155°C to 170°C. In some technical solutions, the temperature of the hydrothermal reaction is 160°C to 170°C. As an example, the temperature of the hydrothermal reaction can be, but is not limited to, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C. The time of the hydrothermal reaction is 12h to 36h. In some technical solutions, the time of the hydrothermal reaction is 14h to 32h. In some technical solutions, the time of the hydrothermal reaction is 16h to 28h. In some technical solutions, the time of the hydrothermal reaction is 20h to 24h. As an example, the time of the hydrothermal reaction can be, but is not limited to, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, 30 h, 32 h, 34 h, or 36 h.

[0046] The present invention firstly adjusts the pH of the reaction solution to 8-12 by alkali, and then reacts at 140-180°C for 14-32 hours. Under this condition, tin chloride pentahydrate and nickel chloride hexahydrate are dissolved in water to form corresponding metal ions (Sn 2+ and Ni 2+ ), while Sn 2+ and Ni 2+ With OH in aqueous solution - interact and combine together to form NiSn(OH)6 precipitate, which is the precursor.

[0047] Washing includes alcohol washing and water washing. In some technical solutions, alcohol washing includes washing and filtering the reaction product multiple times with ethanol, and water washing includes washing and filtering the reaction product multiple times with deionized water. The drying temperature is 120°C to 150°C. In some technical solutions, the drying temperature is 120°C to 145°C. In some technical solutions, the drying temperature is 125°C to 140°C. As an example, the drying temperature can be but is not limited to 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, and 150°C. The drying time is 8h to 12h. As an example, the drying time can be but is not limited to 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, and 12h.

[0048] In step (2), the mass ratio of the precursor to the selenium powder is 1:1-4. In some technical solutions, the mass ratio of the precursor to the selenium powder is 1:1-3. In some technical solutions, the mass ratio of the precursor to the selenium powder is 1:2-4. In some technical solutions, the mass ratio of the precursor to the selenium powder is 1:2-3. As an example, the mass ratio of the precursor to the selenium powder can be, but is not limited to, 1:1, 1:2, 1:3, 1:4.

[0049] The temperature of the calcination reaction is 400°C to 800°C. In some technical solutions, the temperature of the calcination reaction is 420°C to 765°C. In some technical solutions, the temperature of the calcination reaction is 450°C to 745°C. In some technical solutions, the temperature of the calcination reaction is 500°C to 600°C. As an example, the temperature of the calcination reaction can be, but is not limited to, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, and 800°C. The heating rate is 1°C / min to 10°C / min. In some technical solutions, the heating rate is 2°C / min to 9°C / min. In some technical solutions, the heating rate is 3°C / min to 8°C / min. In some technical solutions, the heating rate is 3°C / min to 6°C / min. As an example, the heating rate can be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min. The insulation time is 1h to 6h. In some technical solutions, the insulation time is 2h to 5h. As an example, the insulation time can be, but is not limited to, 1h, 2h, 3h, 4h, 5h, and 6h. The inert atmosphere includes at least one of nitrogen, argon, helium, and neon. In some technical solutions, the inert atmosphere is selected from nitrogen, in some technical solutions, the inert atmosphere is selected from argon, in some technical solutions, the inert atmosphere is selected from helium, and in some technical solutions, the inert atmosphere is selected from neon.

[0050] The present invention firstly mixes the precursor and selenium powder in a mass ratio of 1:1 to 4, and performs calcination reaction at 400° C. to 800° C. Under this condition, the selenium powder sublimates into a gaseous state and fully contacts and reacts with the precursor to obtain the nickel selenide / tin selenide heterojunction composite material of the present invention.

[0051] The nickel selenide / tin selenide heterojunction composite material of the present invention or the nickel selenide / tin selenide heterojunction composite material prepared by the aforementioned preparation method of the present invention is applied to the negative electrode material of the sodium ion battery, which can effectively improve the conductivity of electrons and ions and has excellent sodium ion storage performance and cycle stability.

[0052] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0053] Example 1

[0054] This embodiment provides a method for preparing a nickel selenide / tin selenide heterojunction composite material, comprising the steps of:

[0055] (1) 3 mmol of nickel chloride hexahydrate and 3 mmol of tin chloride pentahydrate were dissolved in 50 ml of deionized water to form a reaction solution, and then sodium hydroxide was added to adjust the pH of the reaction solution to 10. The reaction solution was poured into a 100 ml Teflon autoclave and reacted at 160° C. for 24 h. The reaction solution was cooled to room temperature, washed, and dried to obtain a precursor;

[0056] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:3 and placed in a tube furnace. The temperature was raised to 500° C. at a heating rate of 2° C. / min under a nitrogen atmosphere for 2 h to obtain a nickel selenide / tin selenide heterojunction composite material.

[0057] Example 2

[0058] This embodiment provides a method for preparing a nickel selenide / tin selenide heterojunction composite material, comprising the steps of:

[0059] (1) 3 mmol of nickel chloride hexahydrate and 1.5 mmol of tin chloride pentahydrate were dissolved in 50 ml of deionized water to form a reaction solution, and then sodium hydroxide was added to adjust the pH of the reaction solution to 12. The reaction solution was poured into a 100 ml Teflon autoclave and reacted at 160° C. for 36 hours. The reaction solution was cooled to room temperature, washed, and dried to obtain a precursor;

[0060] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:1 and placed in a tube furnace. The mixture was heated to 600°C at a heating rate of 3°C / min under an argon atmosphere for 3 hours to obtain a nickel selenide / tin selenide heterojunction composite material.

[0061] Example 3

[0062] This embodiment provides a method for preparing a nickel selenide / tin selenide heterojunction composite material, comprising the steps of:

[0063] (1) dissolving 2 mmol of nickel chloride hexahydrate and 2 mmol of tin chloride pentahydrate in 50 ml of deionized water to form a reaction solution, and then adding sodium hydroxide to adjust the pH of the reaction solution to 10. The reaction solution is poured into a 100 ml Teflon autoclave and reacted at 180° C. for 12 h. After cooling the reaction solution to room temperature, the reaction solution is washed and dried to obtain a precursor.

[0064] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:4 and placed in a tube furnace. The mixture was heated to 800° C. at a heating rate of 8° C. / min in a helium atmosphere and reacted for 6 h to obtain a nickel selenide / tin selenide heterojunction composite material.

[0065] Example 4

[0066] This embodiment provides a method for preparing a nickel selenide / tin selenide heterojunction composite material, comprising the steps of:

[0067] (1) dissolving 1 mmol of nickel chloride hexahydrate and 4 mmol of tin chloride pentahydrate in 50 ml of deionized water to form a reaction solution, and then adding sodium hydroxide to adjust the pH of the reaction solution to 9. The reaction solution was poured into a 100 ml Teflon autoclave and reacted at 140° C. for 36 hours. After cooling the reaction solution to room temperature, the reaction solution was washed and dried to obtain a precursor.

[0068] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:2 and placed in a tube furnace. The mixture was heated to 600°C at a heating rate of 5°C / min in a neon atmosphere for 3 hours to obtain a nickel selenide / tin selenide heterojunction composite material.

[0069] Example 5

[0070] This embodiment provides a method for preparing a nickel selenide / tin selenide heterojunction composite material, comprising the steps of:

[0071] (1) dissolving 2 mmol of nickel chloride hexahydrate and 4 mmol of tin chloride pentahydrate in 50 ml of deionized water to form a reaction solution, and then adding sodium hydroxide to adjust the pH of the reaction solution to 10. The reaction solution was poured into a 100 ml Teflon autoclave and reacted at 180° C. for 36 hours. After cooling the reaction solution to room temperature, the reaction solution was washed and dried to obtain a precursor.

[0072] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:2 and placed in a tube furnace. The temperature was raised to 600°C at a heating rate of 5°C / min in a helium atmosphere for 2 hours to obtain a nickel selenide / tin selenide heterojunction composite material.

[0073] Example 6

[0074] This embodiment provides a method for preparing a nickel selenide / tin selenide heterojunction composite material, comprising the steps of:

[0075] (1) dissolving 2.5 mmol of nickel chloride hexahydrate and 5 mmol of tin chloride pentahydrate in 50 ml of deionized water to form a reaction solution, and then adding sodium hydroxide to adjust the pH of the reaction solution to 11. The reaction solution was poured into a 100 ml Teflon autoclave and reacted at 140° C. for 24 h. After cooling the reaction solution to room temperature, the reaction solution was washed and dried to obtain a precursor.

[0076] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:2 and placed in a tube furnace. The mixture was heated to 500°C at a heating rate of 5°C / min under an argon atmosphere for 2 hours to obtain a nickel selenide / tin selenide heterojunction composite material.

[0077] Figure 1 This is a SEM image of the nickel selenide / tin selenide heterojunction composite material prepared in this example. It can be seen from the figure that it is composed of a large number of ultra-thin nanosheets and has a flower ball morphology structure with a diameter of 5.0μm to 6.0μm.

[0078] Figure 2 This is the XRD spectrum of the nickel selenide / tin selenide heterojunction composite material prepared in this example. It can be observed from the figure that the main diffraction peaks match well with the diffraction peaks of tin selenide and nickel selenide.

[0079] Figure 3 and Figure 4 HRTEM spectra of the nickel selenide / tin selenide heterojunction composite material prepared in this example at different magnifications. From the figure, an obvious heterogeneous interface between nickel selenide / tin selenide can be observed, indicating the existence of rich phase boundaries.

[0080] Figure 5 This is a long cycle performance curve of the nickel selenide / tin selenide heterojunction composite material prepared in this embodiment. From the figure, it can be observed that after 500 cycles at a current density of 2A / g, the nickel selenide / tin selenide heterojunction composite material provides a high specific capacity of 392.6mAh g-1 and exhibits good stability.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing nickel selenide, comprising the steps of:

[0083] (1) dissolving 2.5 mmol of nickel chloride hexahydrate in 50 ml of deionized water to form a reaction solution, and then adding sodium hydroxide to adjust the pH of the reaction solution to 11. The reaction solution was poured into a 100 ml Teflon autoclave and reacted at 140° C. for 24 h. After cooling the reaction solution to room temperature, the reaction solution was washed and dried to obtain a precursor.

[0084] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:2 and placed in a tube furnace. The temperature was raised to 500° C. at a heating rate of 5° C. / min under an argon atmosphere for 2 h to obtain nickel selenide.

[0085] Comparative Example 2

[0086] This comparative example provides a method for preparing tin selenide, comprising the steps of:

[0087] (1) 5 mmol of tin chloride pentahydrate was dissolved in 50 ml of deionized water to form a reaction solution, and then sodium hydroxide was added to adjust the pH of the reaction solution to 11. The reaction solution was poured into a 100 ml Teflon autoclave and reacted at 140° C. for 24 h. The reaction solution was cooled to room temperature, washed, and dried to obtain a precursor;

[0088] (2) The precursor and selenium powder were mixed evenly in a mass ratio of 1:2 and placed in a tube furnace. The temperature was raised to 500° C. at a heating rate of 5° C. / min under an argon atmosphere for 2 h to obtain tin selenide.

[0089] The materials prepared in Examples 1 to 6 and Comparative Examples 1 to 2, conductive carbon black (SP) and polyvinylidene fluoride (PVDF) were dispersed in a beaker containing N-methylpyrrolidone (NMP) solvent in a mass ratio of 7:2:1, heated and stirred to fully dissolve them, and stirred for 12 hours to prepare a slurry with good fluidity. After mixing evenly, the slurry was evenly coated on a copper foil to form an electrode. Subsequently, the electrode sheet was dried at 60°C under vacuum for 12 hours to ensure that the NMP was completely volatilized. Finally, the electrode was cut into a working electrode with a diameter of 12 mm after rolling, and the active material mass loading of each electrode was approximately 1.5 mg / cm 2 .

[0090] CR 2025 button cells (including positive and negative electrode shells, shrapnel, and gasket) were used for assembly. The operation process was carried out in a glove box filled with inert gas argon with water and oxygen content less than 0.1ppm. The positive electrode shell, working electrode, electrolyte, glass fiber diaphragm, metal sodium sheet, gasket, shrapnel, and negative electrode shell were assembled in this order, and then packaged using a battery packaging machine. After packaging, it was placed in a 25°C constant temperature box for standby use. The prepared sodium ion batteries were respectively subjected to 500 long cycle tests using Wuhan Landian LANDCT 3002A charge and discharge test cabinet at a voltage range of 0-3.0V and a current density of 2A / g; the button battery's first charge specific capacity (mAh / g) and the charge specific capacity (mAh / g) after 500 cycles of charge and discharge were detected, and the test results are shown in Table 1.

[0091] The charge transfer resistance was measured using an electrochemical workstation at 0.01 Hz to 10 5 The value is obtained by electrochemical impedance testing of the battery in the Hz frequency range.

[0092] Table 1 Performance test results of Examples 1 to 6 and Comparative Examples 1 to 2

[0093]

[0094] Specifically, as shown in the test results of Table 1, it can be seen from the test results of Examples 1 to 6 and Comparative Examples 1 to 2 that the nickel selenide / tin selenide heterojunction composite material prepared by the present invention is applied to the negative electrode material of a sodium ion battery, and its initial charge capacity is 350mAh / g to 450mAh / g, and the charge capacity after 500 cycles is 300mAh / g to 400mAh / g, and the charge transfer resistance is 5Ω to 30Ω. The results show that the nickel selenide / tin selenide heterojunction composite material of the present invention can effectively improve the conductivity of electrons and ions, and has excellent sodium ion storage performance and cycle stability.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A nickel selenide / tin selenide heterojunction composite material, characterized in that: The structure has a flower ball morphology, which is formed by stacking a number of nanosheets. The nanosheets include nickel selenide and tin selenide loaded on the surface of the nickel selenide, and the connection interface between the nickel selenide and the tin selenide forms a heterojunction.

2. The nickel selenide / tin selenide heterojunction composite material according to claim 1, characterized in that: Includes at least one of the following features (i) to (viii): (1) The diameter of the flower ball structure is 2 μm to 8 μm; (ii) the thickness of the nanosheet is 50 nm to 100 nm; (iii) the thickness of the tin selenide is 5 nm to 15 nm; (iv) the nickel selenide d(131) = 0.195 nm; (V) the tin selenide d(040) = 0.291 nm; (vi) The first charge specific capacity of the nickel selenide / tin selenide heterojunction composite material is 350 mAh / g to 450 mAh / g; (VII) The specific charge capacity of the nickel selenide / tin selenide heterojunction composite material after 500 cycles is 300 mAh / g to 400 mAh / g; (VIII) The charge transfer resistance of the nickel selenide / tin selenide heterojunction composite material is 5Ω to 30Ω.

3. A method for preparing a nickel selenide / tin selenide heterojunction composite material, characterized in that: Includes steps: (1) dissolving tin chloride pentahydrate and nickel chloride hexahydrate in water to form a reaction solution, adding alkali to adjust the pH of the reaction solution to 8 to 12, and then performing a hydrothermal reaction. After the reaction is completed, the reaction solution is cooled to room temperature, washed, and dried to obtain a precursor; (2) The precursor and selenium powder are uniformly mixed and then calcined in an inert atmosphere to obtain a nickel selenide / tin selenide heterojunction composite material.

4. The method for preparing the nickel selenide / tin selenide heterojunction composite material according to claim 3, characterized in that: The molar ratio of the tin chloride pentahydrate to the nickel chloride hexahydrate is 1:0.5-4.

5. The method for preparing the nickel selenide / tin selenide heterojunction composite material according to claim 3, characterized in that: The alkali is selected from at least one of sodium hydroxide and potassium hydroxide.

6. The method for preparing the nickel selenide / tin selenide heterojunction composite material according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 140° C. to 180° C., and the time of the hydrothermal reaction is 12 h to 36 h.

7. The method for preparing the nickel selenide / tin selenide heterojunction composite material according to claim 3, characterized in that: The washing includes alcohol washing and water washing, the drying temperature is 120° C. to 150° C., and the drying time is 8 h to 12 h.

8. The method for preparing the nickel selenide / tin selenide heterojunction composite material according to claim 3, characterized in that: The mass ratio of the precursor to the selenium powder is 1:1-4.

9. The method for preparing the nickel selenide / tin selenide heterojunction composite material according to claim 3, characterized in that: The inert atmosphere includes at least one of nitrogen, argon, helium and neon. The calcination reaction temperature is 400°C to 800°C, the heating rate is 1°C / min to 10°C / min, and the insulation time is 1h to 6h.

10. Use of the nickel selenide / tin selenide heterojunction composite material according to any one of claims 1 to 2 or the nickel selenide / tin selenide heterojunction composite material prepared according to the method for preparing the nickel selenide / tin selenide heterojunction composite material according to any one of claims 3 to 9 as a negative electrode material for a sodium ion battery.